Pembelajaran Kontekstual Jarak Antar Titik pada Kubus dengan Pendekatan Realistic Mathematics Education (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Realistic Mathematics Education (RME) is an effective approach to improve mathematics learning outcomes while providing students with opportunities to gain real experience in understanding mathematical concepts. Data analysis used by comparing two cycles obtained from student learning evaluation results. The results of the study illustrate that there was a significant increase after using a realistic approach. This study aims to improve the understanding of the concept of distance between points in MA AISYIYAH PALEMBANG students using a realistic approach. This method uses the Class Level Approach (CAR) research method which is carried out in two cycles. Data were collected through conceptual understanding, observation, and documentation.